2019
DOI: 10.1021/acsomega.9b02674
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of PVDF/PVDF-g-PEGMA Ultrafiltration Membranes by Partial Solvent Substitution with Green Solvent Dimethyl Sulfoxide during Fabrication

Abstract: Traditional organic solvents used in membrane manufacturing, such as dimethylformamide and tetrahydrofuran, are generally very hazardous and harmful to the environment and human health. Their total or partial substitution with green solvent dimethyl sulfoxide (DMSO) is proposed to fabricate membranes composed of poly(vinylidene fluoride) (PVDF) blended with PVDF-graft-poly(ethylene glycol) methyl ether methacrylate (PEGMA), with the purpose to accomplish a greener chemical process and enhance the membrane perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…The flux recovery ratio (FRR), total flux decline ratio (DR t ), reversible flux decline ratio (DR r ), and irreversible flux decline ratio (DR ir ) were calculated with the following equations using an average value from separate tests for each membrane sample. 26 , 31 …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flux recovery ratio (FRR), total flux decline ratio (DR t ), reversible flux decline ratio (DR r ), and irreversible flux decline ratio (DR ir ) were calculated with the following equations using an average value from separate tests for each membrane sample. 26 , 31 …”
Section: Materials and Methodsmentioning
confidence: 99%
“…In the previous study, we found that membranes with enhanced hydrophilicity were fabricated by changing the polymer concentration in the casting solution. 26 Following this line of thought, two superwettable modified PVDF membranes were successfully fabricated using lower polymer concentration in this study, the achieved outstanding improvement in wettability were studied and the relevant effects accounting for this phenomenon were investigated in details. In particular, chemical, physical, and structural features were studied and their combined influence on the surface wettability behavior was rationalized within the Wenzel model of wetting.…”
Section: Introductionmentioning
confidence: 99%
“…15 During the past decade, several green solvents have been proposed for PVDF membrane fabrication, including glycerol triacetate (triacetin), 16,17 maleic acid dibutyl ester, 18 triethylene glycol diacetate, 19 acetyl tributyl citrate, 11 tributyl citrate, 20 methyl-5-(dimethylamino)-2-methyl-5-oxopentanoate (Polarclean®), 21,22 Cyrene®, 23 dimethyl isosorbide, 24 and ionic liquids (ILs). 25 Wu et al 26 adopted the strategy of mixing the toxic solvent with a green solvent to decrease the negative environmental impact of the preparing ultrafiltration membranes. However, two factors must be considered when evaluating these reports and the suitability of green solvents for PVDF membrane fabrication.…”
Section: Polymorph Phasementioning
confidence: 99%
“…As can be seen from Table S1, using graft copolymer in the dope solution can sometimes be very effective at improving the pure water permeances of PVDF-NIPS membranes. [32][33][34][35] But the mechanical strengths of the membrane deteriorate significantly because of the formation of the undesirably large macrovoids in its crosssection. [35][36][37] Its pore size distribution is also wide with pore sizes ranging from 20-160nm.…”
Section: Introductionmentioning
confidence: 99%